Whistler on a Shelf. Issue 5 (13th May 2021) - Streltsov, Anatoly V.
Abstract: This study presents results from a numerical study of the guiding of VLF whistler‐mode waves along the ambient magnetic field by the shelf‐like density structures observed by the NASA Van Allen Probes satellites in the equatorial plasmasphere. The shelf‐duct consists of a homogeneous central part "sandwiched" between two density gradients pointing in the same direction. To the best of our knowledge, this type of whistler ducting has never been identified in observations before. Our investigation is based on simulations of the electron‐MHD model, and our goal is to explain the mechanism of providing wave trapping and to reproduce the structure of the observed waves. The main result from this study is that the shelf‐like, field‐aligned density irregularities can indeed guide whistler‐mode waves along the ambient magnetic field with little attenuation, and the parameters of the guided waves are defined by the parameters of the duct. The simulations reproduce the structure of the observed waves reasonably well. Key Points: We investigate propagation of the whistler‐mode waves in the equatorial plasmasphere We show that whistlers can be guided by the shelf‐like density structures Our simulations reproduce the structure of the guided waves observed by the RBSP satellites